Enhancing public health in developing nations through smartphone-based motor assessment - Souza, Givago Silva; Furtado, Brena Karoline Ataíde; Almeida, Edilson Brabo; Callegari, Bianca; Pinheiro, Maria da Conceição Nascimento (Frontiers in Digital Health, 2024)
Several protocols for motor assessment have been validated for use on smartphones and could be employed by public healthcare systems to monitor motor functional losses in populations, particularly those with lower income levels. In addition to being cost-effective and widely distributed across populations of varying income levels, the use of smartphones in motor assessment offers a range of advantages that could be leveraged by governments, especially in developing and poorer countries. Some topics related to potential interventions should be considered by healthcare managers before initiating the implementation of such a digital intervention.